The Formal Total Synthesis of FR252921 – An Immunosuppressant. Issue 2 (15th November 2012) - Yadav, J. S.; Sengupta, Sandip
Abstract: The formal total synthesis of FR252921 is described. The key steps include the preparation of three fragments starting from 1, 4‐butanediol, ( R )‐malic acid, and prenol, respectively, followed by two consecutive peptide couplings of the three fragments. Other key steps involve an allene‐type rearrangement or enyne isomerization to install the triene moiety, a Seebach methylation, a Julia olefination to construct the trisubstituted diene unit, and an enzymatic resolution strategy to generate the C‐18 stereocenter. Abstract : The formal total synthesis of FR252921 is described. The key steps include the preparation of three fragments starting from 1, 4‐butanediol, ( R )‐malic acid, and prenol, respectively, followed by two consecutive peptide couplings of the three fragments.